Evaluating and planning for interdisciplinary collection development: a case of an East Asian collection at the College of Staten Island Library. Issue 2 (7th April 2015) - Dzurak, Ewa; Falloon, Kerry A.; Cope, Jonathan
Abstract : Purpose: – The purpose of this article is to examine the challenges of collection analysis and development in response to a new academic interdisciplinary program in East Asian Studies at the College of Staten Island, City University of New York. Design/methodology/approach: – First, the authors examined the needs of a new East Asian Studies program and its interdisciplinary nature. Next, an automated collection development tool was chosen that provides a snapshot of current monograph holdings and a comparison with other equivalent institutions. Lastly, the authors conduct an analysis of citations in key Asian Studies journals, library holdings in relevant top electronic resources and core journal subscriptions. For future collection building, vendor tools and patron-drive acquisitions are explored. Findings: – Traditional methods of collection development can prove inadequate. A variety of tools and methods need to be used to guarantee adequate results. Originality/value: – This paper builds on prior research related to developing interdisciplinary collections by using traditional methods of collection development with critical judgments.